Comparative analysis of chloroplast genomes and phylogenetic relationships in the endemic Chinese bamboo Gelidocalamus (Bambusoideae) - Wang, Chengkun; Li, Yonglong; Yang, Guangyao; Zhang, Wengen; Guo, Chunce (Frontiers in Plant Science, 2024)
Gelidocalamus Wen is a small but taxonomically challenging genus within the Arundinarieae tribe.Recent molecular studies have suggested it may not be monophyletic. However, limited species sampling and insufficient molecular marker information have resulted in poorly resolved phylogenetic relationships within this genus. In this study, we sequenced the complete chloroplast genomes covering all 16 species and one variant within the genus. Additionally, we assembled a nrDNA repeats region and 29 mitochondrial protein-coding genes from the genome skimming data. The plastomes of Gelidocalamus ranged in size from 139,500 to 139,801 bp, with a total of 137 genes identified, including 90 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. The size of the nrDNA repeats ranged from 5802 to 5804 bp. Phylogenetic analysis based on chloroplast data revealed that Gelidocalamus is polyphyletic, with different subclades distributed within the IV and V clades.However, phylogenetic analysis based on nrDNA and mitochondrial genes did not resolve the relationships within the genus effectively. Comparative analysis of chloroplast genomes indicated that Gelidocalamus shares a high degree of similarity with closely related genera in terms of chloroplast genome collinearity, codon usage bias, and repetitive sequences. Divergence time estimation suggested that it is a relatively young group, with all members appearing successively over the past 4 million years. The complex phylogenetic patterns may arise due to rapid radiation of Arundinarieae. This study provides a preliminary foundation for further in-depth research on the phylogeny, genomic structural features, and divergence times of this genus.